Verbalizing the Concept of Freedom in the Cold War U.S. Political Discourse - Kalishchuk, Diana; Lazuka, Oleksandr (East European Journal of Psycholinguistics, 2015)
The article describes the peculiarities of verbalization of the concept FREDOOM as one of the basic concepts in American political discourse in the period of “Cold War”. The concept is viewed as a cognitive phenomenon. The analysis of the concept FREDOOM is carried out on the material of political discourse as one of the types of institutional discourse in which the sender and recipient acquire certain social roles, depending on their participation in political life. The description of the concept is carried out by constructing the nominative field of the concept, namely: the core and the periphery. The article covers the analysis of the structure of the core, which was conducted in two stages. During the first stage the core of the concept in the professional politicians’ discourse was built, language means for which were selected from the speeches of political leaders. During the second stage, the core of the concept under consideration was built in the discourse of ordinary citizens. The linguistic means for that stage of investigation were collected from respondents-voters by interviewing, using the method of synonymic replacement. The analysis allowed to distinguish and describe the similarities and differences in the core of the concept FREEDOM in the discourse of politicians-professionals and voters – ordinary citizens, enabled to define the relationship and connection of characteristics of the investigated core with geopolitical events. References Babushkin, A. (1998) Ob’yektivnoye i Sub’yektivnoye v Kategorizatsii Mira [Objective and Subjective in the Categorization of the World]. Obshchiye Problemy Stroyeniya i Organizatsii Yazykovykh Kategorii, 28–31. Collins English Thesaurus. (2011). Harper Collins Publishers. Denisenko V., Klimonchuk V., Pryvalov Yu. (2007). Dyskurs Svobody: Utopiya Chi Realnist Vyboru [The Discourse of Freedom: Utopia or the Reality of Choice]. Lviv: Astrolyabíya. Extract from George Bush and Tony Blair’s press conference at the White House. (2006). Retrieved from: http://www.theguardian.com/world/2006/may/26/politics.usa. Leontyev, A., Shakhnarovich, A. (1983) Psikholingvisticheskiye Problemy Semantiki [Psycholinguistic Problems of Semantics]. Moscow: Nauka. Longman Dictionary of Contemporary English. (2000). Edinburgh Gate, Harlow: Pearson Education. Maslova, V. (2001) Lingvokulturologiya [Linguistic Cultural Studies]. Moscow: Akademiya. Merriam-Webster’s Dictionary and Thesaurus. (2006). Springfield, Massachusetts, USA. Oxford Advanced Learner’s Dictionary. (2001). Oxford: Oxford University Press. Popova, Z., Sternin, I. (2002) Yazyk i Natsionalnoye Soznanie. Voprosy Teorii i Metodologii [Language and National Consciousness. Issues of Theory and Methodology]. Voronezh: Voronezh Humanitarian University. Prikhodko, A. (2008) Kontsepty i Kontseptosystemy v Kohnityvno-Dyskursyvnii Paradyhmi Línhvistyky [Concepts and Contseptosystems in Cognitive-Discursive Paradigm in Linguistics]. Zaporizhzhya: Premyer. Telia V. (1996). Rol’ Obraznykh Sredstv Yazyka v Kulturno-Natsyonalnoy Okraske Miroponimaniya [The Role of Figurative Means of Language in Cultural and National Coloring of the Worldview]. Étnopsikholingvisticheskie Aspekty Prepodavniia Inostrannykh Yazykov, 85–87. The Miller Center. (2015). Retrieved from: http://millercenter.org/. Webster’s Third New International Dictionary of the English Language. (1986). Springfield, Massachusetts, USA.